PENGARUH PENGGUNAAN METODE PROBLEM BASED LEARNING UNTUK MENINGKATKAN HASIL BELAJAR PADA PEMBELAJARAN SENI MUSIK DI SMA NEGERI 1 LEMBAH MELINTANG PASAMAN BARAT - Humaira, Delvia; Sudarman, Yos (Avant-garde: Jurnal Ilmiah Pendidikan Seni Pertunjukan, 2026)
This study aims to determine the differences in music learning outcomes between students taught using the Problem Based Learning method and those taught using conventional methods, as well as the differences in the implementation of the Problem Based Learning method on the improvement of music learning outcomes of XI grade students at SMAN 1 Lembah Melintang. The type of research used by the researcher is a quasi-experiment with a pretest post test nonequivalent control group design. The population of this study is the XI grade students of the even semester at SMAN 1 Lembah Melintang, West Pasaman, totaling 60 students, and the sample was taken using purposive sampling. Data was collected through written tests, observations, and documentation. The data analysis techniques in this study include analysis of the learning implementation sheets, normalized gain analysis, prerequisite hypothesis testing, and hypothesis testing. The research results indicate that the implementation of the Problem Based Learning model has a positive and significant effect on students' cognitive learning outcomes and music art skills. Students' cognitive learning outcomes in music art lessons using the Problem Based Learning model are higher compared to those of students who follow lessons using conventional methods. This is evidenced by the results of an independent two-sample t-test, which showed a significant value (Sig. 2-tailed) of less than 0.05, indicating a significant difference between the experimental and control classes. The normalized gain (N-Gain) analysis shows that the improvement in students' learning outcomes in the experimental class falls into the medium to high category, whereas in the control class it falls into the low to medium category. These findings indicate that the application of the Problem Based Learning model is more effective in enhancing the understanding of music concepts compared to conventional teaching methods. Assessment results of music skills show that the average skills of students in the experimental class are higher than in the control class. This demonstrates that learning through the Problem Based Learning model can improve students' vocal skills in terms of mastery of material, expression, and confidence in presenting learning outcomes.